2021
DOI: 10.1002/adom.202100027
|View full text |Cite
|
Sign up to set email alerts
|

Direct Laser Writing for the Formation of Large‐Scale Gold Microbumps Arrays Generating Hybrid Lattice Plasmon Polaritons in Vis–NIR Range

Abstract: Surface plasmon polaritons (SPPs) based light–matter interactions play a major role in photonic sensor applications. In order to implement such sensors in microchip devices or reduce the fabrication costs, a method with high flexibility and large‐scale capabilities must be developed. Here, the formation of large‐scale gold microbumps arrays by using a direct laser writing technique is presented. The fabricated arrays exhibit the hybrid lattice plasmon polaritons in the Vis–NIR range, in the same range as metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…However, the inverse system under total internal reflection does not generate the lattice plasmon resonances which have been widely reported on various metallic subwavelength structures under traditional reflection. 23,28 Another optical phenomenon which is related to gratings is the Rayleigh Anomaly (RA), which sometimes leads to a narrower spectral width, 38 however, it was demonstrated that the coupling between the RA and SPPs can occur only for the range of the film thickness. 39…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the inverse system under total internal reflection does not generate the lattice plasmon resonances which have been widely reported on various metallic subwavelength structures under traditional reflection. 23,28 Another optical phenomenon which is related to gratings is the Rayleigh Anomaly (RA), which sometimes leads to a narrower spectral width, 38 however, it was demonstrated that the coupling between the RA and SPPs can occur only for the range of the film thickness. 39…”
Section: Resultsmentioning
confidence: 99%
“…Another way to obtain the narrow plasmonic resonances with fewer losses has been demonstrated by using metallic grating arrays. 13 Current lithography methods 22 or direct laser writing (DLW) 23 enable the creation of complex plasmonic systems supporting multiple plasmon modes. The most popular nanostructures of complex plasmonic systems are metallic nanoparticle arrays, whose period is comparable with the incident light wavelength.…”
Section: Introductionmentioning
confidence: 99%
“…The discrepancy may be related to the rather thin film thickness together with the graded doping; as a consequence, the fit allows many different solutions of similar quality, yet none could be found with optimal agreement. Besides, the line shape of the spectrum can be affected by the measurement conditions, such as the brilliance of the light source [50,51], the maximum angle of acceptance of the detector [52]. One must carefully examine the experimental and instrumental conditions used during the measurement of the reflectance spectra, from which the broadband permittivity of the material is deducted.…”
Section: (B)mentioning
confidence: 99%
“…Meanwhile, the subsequent works revealed the key role of the CPRs in the response of the nanobump (nanojet) arrays observed in the near- and mid-IR spectral ranges [ 26 ]. Such versatile easy-to-fabricate plasmonic metasurfaces were proved to be useful for biosensing [ 26 , 27 , 28 ], boosting nonlinear effects [ 29 ] and empowering the light-emitting properties of an attached layer composed of IR quantum dots [ 30 ].…”
Section: Introductionmentioning
confidence: 99%